CO2 emissions of tropical peat soils under controlled groundwater table depths: A laboratory-based experiment - Mahardika, Rabbirl Yarham; Anshari, Gusti Zakaria; Suryadi , Urai Edi (Brawijaya University, 2024)
The groundwater table (GWT) is widely recognized as a key factor influencing CO2 emissions in tropical peatlands. However, previous studies investigating this relationship have reported diverse results. This variability likely stems from the dynamic nature of field-based groundwater conditions. To address this, our study investigated the relationship between controlled GWT and CO2 emissions in a laboratory experiment using PVC columns filled with peat soil. GWT depths were adjusted to 20 cm, 30 cm, 40 cm, 50 cm, and 60 cm within a large container filled with peat pore water. CO2 emissions were measured using an Infra Red Gas Analyzer - Environmental Gas Monitoring-4 instrument, with a closed-chamber system. Our findings revealed significant differences in CO2 emissions between treatments, except for the transition from 20 cm to 30 cm GWT. Correlation analysis showed a positive correlation (R² = 0.25). Notably, CO2 emission factor values based on average yearly emission rates displayed a substantial increase with decreasing GWT, exhibiting a strong exponential relationship (R² = 0.99).